2015
DOI: 10.1007/s11356-015-4806-y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and photocatalysis of nanocrystalline TiO2 particles for Reactive Red 195 removal: effect of humic acids, anions and scavengers

Abstract: In the present study, the coupling of adsorption capacity and photocatalytic efficiency of two different industrially produced titania catalysts was investigated and compared. The azo dye Reactive Red 195 was selected as a model compound. The tested catalysts, PK-10 and PK-180, exhibited different adsorption capacities due to their significant difference in their specific surface, but both have proven to be effective photocatalysts for photodegradation of the studied dye. PK-10 exhibited strong adsorption of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…The lowest removal rate was observed for DCF in the presence of HCO 3 -anions. The presence of Fe 3+ cations inhibited the reaction course of the compound decomposition in all tested micropollutant solutions.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The lowest removal rate was observed for DCF in the presence of HCO 3 -anions. The presence of Fe 3+ cations inhibited the reaction course of the compound decomposition in all tested micropollutant solutions.…”
Section: Resultsmentioning
confidence: 89%
“…1d). The addition of HCO 3 -as well as HPO 4 2-decreased the efficiency of the process and the obtained removal rates for this compound did not exceed 88% after 5 min of UV irradiation. In case of Cl -and SO 4 2-ions did the removal rate for BaP reach 99%.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The process of micropollutants adsorption may be hindered by the presence of organic or inorganic compounds that block active centres on the catalyst surface. Chládková et al [12] indicated that common inorganic anions Cl − , NO − 3 and SO 2− 4 can be competitively adsorbed on the surface of the photocatalyst and decrease the photodegradation rate of organic caompunds. On the other hand, some inorganic compounds such as sulfate ions can be immobilized on the surface of TiO 2 nanoparticles and improve the photocatalytic activity of the formed composite [13].…”
Section: Introductionmentioning
confidence: 99%